2018
DOI: 10.3390/ma11061049
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic View of Defect Evolution in Thermal Treated AlGaInAs Quantum Well Revealed by Spatially Resolved Cathodoluminescence

Abstract: An aluminum gallium indium arsenic (AlGaInAs) material system is indispensable as the active layer of diode lasers emitting at 1310 or 1550 nm, which are used in optical fiber communications. However, the course of the high-temperature instability of a quantum well structure, which is closely related to the diffusion of indium atoms, is still not clear due to the system’s complexity. The diffusion process of indium atoms was simulated by thermal treatment, and the changes in the optical and structural properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The X-ray diffraction pattern of the AlGaInAs QW structure is composed of a dominated InP diffraction peak localized at 63.345 °C (2 theta) and the QW’s multiorder satellite peaks at the side vicinity. More details about the structure property and growth method were presented in our previous work [ 14 ]. The AlGaInAs QW was measured by the temperature-dependent TRPL (HJY TRIX550; Original, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The X-ray diffraction pattern of the AlGaInAs QW structure is composed of a dominated InP diffraction peak localized at 63.345 °C (2 theta) and the QW’s multiorder satellite peaks at the side vicinity. More details about the structure property and growth method were presented in our previous work [ 14 ]. The AlGaInAs QW was measured by the temperature-dependent TRPL (HJY TRIX550; Original, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Huang, et al [ 13 ]. PL decay of the thermal-treated AlGaInAs QW demonstrated that the effect of thermal process had a strong influence on the relaxation time of excitated carriers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation